Evaluation of Faba Beans, White Lupins and Peas as Protein Sources in Broiler Diets - Nalle, C.L.; Ravindran, V.; Ravindran, G. (International Journal of Poultry Science, 2010)
The aim of the present study was to evaluate the effect of the inclusion of faba beans (Vicia faba), white lupins (Lupinus albus) and peas (Pisum sativum) in two different basal diets on the performance, digestive tract development and carcass characteristics of broilers housed in floor pens over a 35 d grow-out period. The experimental design was a 2 x 4 factorial arrangement of treatments which evaluated two basal wheat-soy diets (with or without meat meal) and legume grains (no legume grain, or faba beans, white lupins and peas at 200 g/kg inclusion). All diets were formulated to contain similar levels of metabolizable energy and digestible amino acids. A 3-phase feeding programme (starter, grower and finisher) was employed. The starter, grower and finisher diets were offered from day 1-7, 8-21 and 22-35, respectively. During the starter period, legume x meat meal interaction was significant (p<0.05) for weight gain and feed intake. Birds fed faba bean and white lupin diets containing meat meal had higher (p<0.05) weight gain and feed intake than those without meat meal. During day 1-21, an interaction (p<0.05) between legumes and meat meal was observed for weight gain, with the gain of birds fed the pea diet without meat meal being higher (p<0.05) that than those fed pea diet with meat meal. Over the 35 d trial period, however, with the exception of feed intake, legumes had no effect (p>0.05) on the performance and carcass recovery of broilers and the litter score. Weight gain and feed per gain of birds fed diets without meat meal were better (p<0.05) than those with meat meal. The main effect of legumes was significant (p<0.01 to 0.05) for the relative weight of liver and gizzard and the relative digesta weight of the crop and proventriculus. Birds fed meat meal diets had lower (p<0.05) relative weights of liver, pancreas and small intestine and relative digesta weight of small intestine than those fed diets with no meat meal diets. It was concluded that, when balanced for metabolizable energy and digestible amino acids, dietary inclusion of faba beans, white lupins and peas at 200 g/kg either in wheat-soybean meal or wheat-soybean meal-meat meal basal diets could support a good performance of birds over the 35-day grow-out period.